“Human Beings Are Too Cheap in India”: Wages and Work Organization as Business Strategies in Bombay's Late Colonial Textile Industry - van Nederveen Meerkerk, Elise; Dixit, Aditi (International review of social history, 2025)
This article examines the business strategies employed by early twentieth-century Bombay mill owners in work organization and wage differentiation. The traditionally highly segmented and fluctuating domestic textile markets in India were further complicated by colonial free trade policies, making them highly competitive. This prompted Bombay mills to adopt various strategies, including maintaining a flexible workforce, product diversification, tailoring sales strategies to the Indian market, and increasing labour inputs, related to their heavy reliance on short-stapled Indian raw cotton. Using detailed and disaggregated data reported by textile mills in Bombay during the 1920s and 1930s, this article investigates how employers adopted these strategies in tandem with distinct wage-setting systems as management tools to depress the wage bill. By analysing the motivations behind the adoption of or resistance to these tools across different operations within the production process – such as weaving, spinning, reeling, and winding – the article reveals how gendered and social-class stratifications shaped these strategies and led to wage disparities across the industry. Ultimately, these labour-intensive strategies, conditioned by the broader colonial context in which India's textile industry developed, were at the root of the lower productivity of Indian workers, with long-run adverse consequences for India's general industrial development.